Conflict in the Family and Social Support as determinant of Dialysis Patient’s Compliance - Derasin, Lloyd Matthew C.; Lloyd Vincent C. Derasin (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
The study investigated the relation of dialysis patient’s compliance to the levels of family conflict and the levels of social support. This study utilized the descriptive-correlational design employing quantitative approach in determining if there is a correlation between the Levels of Conflict in the Family, the levels of Social Support and the compliance of the patient. Moreover, the study was conducted in the different dialysis centers in Cebu City and the respondents of the study are the 60 dialysis patients that were selected using a simple random sampling approach. Furthermore, the research instrument used in the study is a researcher made questionnaire. The findings of the study revealed that there was a significant relationship between the Levels of Conflict in the Family and Levels of Social Support to the compliance of the patient. The study concluded that both family and friends are an important fragment in surviving patient on dialysis and they should be flexible on the schedules of the patient and must adjust to the changes in roles and lifestyle